The potential of algae and aquatic macrophytes in the pharmaceutical and personal care products (PPCPs) environmental removal: a review. (September 2022) - Couto, Eduardo; Assemany, Paula Peixoto; Assis Carneiro, Grazielle Cristina; Ferreira Soares, Daniel Cristian
Abstract: The presence of emerging contaminants, such as pharmaceuticals and personal care products (PPCPs), in aquatic environments has received increasing attention in the last years due to the various possible impacts on the dynamics of the natural environment and human health. In global terms, around 771 active pharmaceutical substances or their transformation products have been detected at levels above their respective detection limit. Additionally, 528 different compounds have been detected in 159 countries. Seeking to overcome potential ecotoxicological problems, several studies have been conducted using different technologies for PPCPs removal. Recently, the use of macro, microalgae, and aquatic macrophytes has been highlighted due to the excellent bioremediation capacity of these organisms and easy acclimatization. Thus, the present review aims to outline a brief and well-oriented scenario concerning the knowledge about the bioremediation alternatives of PPCPs through the use of macro, microalgae, and aquatic macrophytes. The characteristics of PPCPs and the risks of these compounds to the environment and human health are also addressed. Moreover, the review indicates the opportunities and challenges for expanding the use of biotechnologies based on algae and aquatic macrophytes, such as studies dedicated to relate the operational criteria of these biotechnologies with the main PPCPs removal mechanisms. Finally, algae and macrophytes can compose green and ecological biotechnologies for wastewater treatment, having great contribution to PPCPs removal. Graphical abstract: Image 1 Highlights: PPCPs impacts are related to intrinsic toxicity, bioaccumulation and persistence. Bioadsorption, biodegradation and uptake play key roles in PPCPs phycoremediation. Interaction of substrate, macrophyte and microorganism is important in wetlands. The removal of PPCPs varies within the configuration of the constructed wetlands. PPCPs removal by algae and macrophytes can be eco-friendly and economically viable.